2017
DOI: 10.1016/s2213-2600(17)30161-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteome analysis in patients with pulmonary arterial hypertension: an observational cohort study

Abstract: SummaryBackgroundIdiopathic and heritable pulmonary arterial hypertension form a rare but molecularly heterogeneous disease group. We aimed to measure and validate differences in plasma concentrations of proteins that are associated with survival in patients with idiopathic or heritable pulmonary arterial hypertension to improve risk stratification.MethodsIn this observational cohort study, we enrolled patients with idiopathic or heritable pulmonary arterial hypertension from London (UK; cohorts 1 and 2), Gies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 31 publications
2
109
1
1
Order By: Relevance
“…CNDP1 was reduced by 43% after RYGB at the 3 month time point (FDR=1.6*10 -5 ) and remained lower in RYGB at 36 months ( Figure 5B). A previous study had been unable to validate SOMAscan CNDP1 measurements (38). ELISA-determined CNDP1 levels in our analysis showed little correlation with SOMAscan levels per time point, but changes within person over time showed stronger correlation (r=0.21, p=0.055).…”
Section: Proteomic and Metabolomic Integrative Pathway Analysiscontrasting
confidence: 80%
“…CNDP1 was reduced by 43% after RYGB at the 3 month time point (FDR=1.6*10 -5 ) and remained lower in RYGB at 36 months ( Figure 5B). A previous study had been unable to validate SOMAscan CNDP1 measurements (38). ELISA-determined CNDP1 levels in our analysis showed little correlation with SOMAscan levels per time point, but changes within person over time showed stronger correlation (r=0.21, p=0.055).…”
Section: Proteomic and Metabolomic Integrative Pathway Analysiscontrasting
confidence: 80%
“…Evaluations of PH cohorts demonstrate a high frequency of ID and/or anaemia in PH patients, as approximately 40-60% of PH patients demonstrate ID and one-third of all PH patients suffer from anaemia [27,28]. Interestingly, both ID and anaemia significantly affect the morbidity and mortality of PH patients [27,29]. Current evidence suggests a significant role of iron handling in the pathogenesis and clinical outcome of both, pre-and post-capillary pulmonary hypertension [4,28,[30][31][32].…”
Section: Interconnection Of Pulmonary Hypertension Iron Homeostasismentioning
confidence: 99%
“…11,12 These studies and other reported molecular phenotyping efforts to date have inherent limitations, as analyses are anchored to specific clinical definitions and PAH subtypes that may not adequately reflect disease heterogeneity. [13][14][15][16][17] 'Unsupervised' phenotyping is a more agnostic strategy, where molecular profiles directly define phenotypes that are subsequently related to clinical characteristics. 18 These molecular phenotypes can be identified by machine learning, which is the inference of substructure in complex unlabeled data with computer algorithms.…”
Section: Introductionmentioning
confidence: 99%